Strategi Siar Dakwah Mar’atus Sholihah Radio 107 FM - Zahra, Upi; Septiani, Indah Nur (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
This study examines the communication strategy of Radio Dakta 107 FM broadcasters in attracting listeners' interest in the Mar'atus Sholihah program. The background of this research is the existence of radio that is still relevant in the digital era. The purpose of this research is to identify the planning, implementation of broadcaster communication strategies and the obstacles faced. Qualitative research methods with a descriptive approach are used to collect data through observation, interviews and documentation. The results of the study show that the communication strategy of Radio Dakta 107 FM broadcasters includes promotion on social media, expanding access through applications and streaming broadcasts, and sharing activities on YouTube. The implementation of this strategy is effective in improving communication with listeners. However, obstacles such as online media competition and technical glitches are a challenge.